INFLUENCE OF SERVANT LEADERSHIP AND PSYCHOLOGY CAPITAL TO EMPLOYEES PERFORMANCE BY AS OF MEDIATION ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) (Studies in District Education OfficeRembang) - HadiSubena, 13.5202.0022; Tjahjaningsih, Endang (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to analyze the effect of servant leadership and psychological capital to performance by as of mediation OCB studiesat theDistrict Education office Rembang. The population inthis studyisa civil servantat the District Education Office Rembang as many as128people, using the "sampling method". a sample to bemade the objectof researchisas much as105employees, andgivingquestionnaires torespondents usingLikert scale(a scale measuringperceptions ofthe respondents), quantitative analysis methodssuch asdescriptive analysisof respondents, descriptive analysisof variables, testing instrumentstestingtest modelof determination, f test, testingdetermination testmodel ofmultiple linear regression analysist-test,mediation(path analysis) and thenanalyzedusingcorrelationandregressioncoefficients. The research provesservant leadershiphas apositive and significant impacton OCB, capitalof psychologydo not have apositive and significant impacton OCB, kepemim-pinan who servehavepositive and significant impacton performance, capital ofpsychologyhas apositive and significant impacton performance, OCBdoes nothas apositive and significant impacton the performanceof employees, Keywords : servant leadership, capital of psychology, organizational citizenship behavior and performance